2005
DOI: 10.1016/j.cardiores.2005.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calsequestrin over-expression on excitation–contraction coupling in isolated rabbit cardiomyocytes

Abstract: CSQ over-expression increased SR Ca2+ content but reduced the gain of E-C coupling in rabbit cardiomyocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…The major findings were that somatic gene transfer of CSQ that is otherwise absent in hESC-CMs renders their Ca 2ϩ -handling properties more mature, as reflected by an increased SR load, an elevated basal cytosolic Ca 2ϩ , augmented Ca 2ϩ -transient amplitude, and accelerated kinetics. Although our observations with hESC-CMs share a number of similarities with previous studies of CSQ in isolated adult CMs (23,24) and transgenic models (14,27), several differences were also noticeable. As further elaborated and discussed below, such similarities and differences can be attributed to their common identities as CMs and different developmental stages, respectively.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The major findings were that somatic gene transfer of CSQ that is otherwise absent in hESC-CMs renders their Ca 2ϩ -handling properties more mature, as reflected by an increased SR load, an elevated basal cytosolic Ca 2ϩ , augmented Ca 2ϩ -transient amplitude, and accelerated kinetics. Although our observations with hESC-CMs share a number of similarities with previous studies of CSQ in isolated adult CMs (23,24) and transgenic models (14,27), several differences were also noticeable. As further elaborated and discussed below, such similarities and differences can be attributed to their common identities as CMs and different developmental stages, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…Our experiments, however, attempted to express the missing protein in hESC-CMs to facilitate the maturation process by rendering their Ca 2ϩ -handling properties adult-like, thereby shedding insights into its developmental and functional roles. For instance, adenovirus-mediated overexpression of CSQ2 in adult rabbit ventricular CMs in vitro has been previously reported to increase the SR Ca 2ϩ content while reducing the excitation-contractin coupling gain (23). Although the Ca 2ϩ load is increased in transgenic mice that overexpress CSQ, however, these animals develop hypertrophy and heart failure with impaired SR Ca 2ϩ release and decreased Ca 2ϩ spark frequency (14,27,36).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with other investigations in which the effect of over-expression of SR/ER high capacity low affinity Ca 2þ binding properties was studied. Indeed chronic over-expression of calsequestrin, the major Ca 2þ binding protein in striated muscle in cardiomyocytes, increased the Ca 2þ storage capacity of the SR but did not affect the expression level of SERCA or phospholamban (Jones et al, 1998;Sato et al, 1998;Knollmann et al, 2000;Miller et al, 2005). Consistent results showing an increase in the lumenal SR Ca 2þ buffering capacity were obtained when the luminal histidine-rich Ca 2þ binding protein (HRC) was over-expressed in neonatal and adult rat cardiomyocytes (Kim et al, 2003;Fan et al, 2004).…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, over-expression of other known calcium storage proteins such as calsequestrin and histidine rich Ca 2þ binding protein leads to an increase in caffeine-induced Ca 2þ release (Jones et al, 1998;Sato et al, 1998;Kim et al, 2003;Fan et al, 2004;Miller et al, 2005). Over-expression of junctate also occurs in a membrane compartment endowed with the RyR Ca 2þ release channel, since we found that (i) direct stimulation of isolated myotubes with either caffeine or 4-CmC resulted in a significantly larger Ca 2þ transient and (ii) total SR microsomes from transgenic mice show a 24% increase of the extent of calcium release induced by 4-CmC.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function Maintains functional SR Ca 2+ storage and increased Viable and display normal Ca 2+ release diastolic SR Ca 2+ leak (67) and contractile function (67) Gain-of-function Increased SR Ca 2+ content but reduced the gain Cardiac hypertrophy and increase of E-C coupling (71) in heart mass (70) (54,55). The adult fast-twitch skeletal muscle expresses exclusively the Casq1 gene, whereas slow-twitch skeletal muscle expresses mainly the Casq1 gene (>75% of total) and to a minor extent the Casq2 gene (>25% of total).…”
Section: Fig 1 Cardiac Muscle Cell Contains Both Sarcoplasmic Reticmentioning
confidence: 99%